The Holy Spirit and the Ongoing Formation of Presbyters - Lipiec, Dariusz (Verbum Vitae, 2020)
The Holy Spirit plays a significant role in the process of the ongoing formation of priests. His activity can be perceived in three aspects. (1) He strengthens the charism given during the ordination to the priesthood in such a way that the presbyter is in constant connection with the Father and with the Son. (2) The Third Person of the Holy Trinity raises anew the pastoral love which is necessary for fulfilling the mission of priesthood and which leads to (3) the deepening of the bond between the priest and God. This enhances the priest's pursuit of his own holiness. The priest should actively respond to the Holy Spirit, Who initiates the contact by his engagement, and he should cooperate with Him for the sake of the salvation of the faithful, in order to build God's Kingdom on earth.